Mast Cell Therapy for Sickel Cell Anaemia - Panwar, Pooja (International Journal of Pharmaceutical & Biological Archive, 2016)
Some sickle cell anaemia (SCA) patients suffer significantly worse phenotypes than others. Causes of such disparities are incompletely understood. Comorbid chronic inflammation likely is a factor. Recently, mast cell (MC) activation (creating an inflammatory state) was found to be a significant factor in sickle pathobiology and pain in a murine SCA model. Also, a new realm of relatively non cytoproliferative MC disease termed MC activation syndrome (MCAS) has been identified recently. MCAS has not previously been described in SCA. Some SCA patients experience pain patterns and other morbidities more congruent with MCAS than traditional SCA pathobiology (eg, vasoocclusion). Presented here are 32 poor-phenotype SCA patients who met MCAS diagnostic criteria; all improved with MCAS-targeted therapy. As hydroxyurea benefits some MCAS patients (particularly SCA-like pain), its benefit in SCA may be partly attributable to treatment of unrecognized MCAS. Further study will better characterize MCAS in SCA and identify optimal therapy.